Morfometrija površja Slovenije - Perko, Drago (Georitem, 2007)
This book describes some basic morphometric characteristics of Slovenia's surface relative to its landscape types using a geographic information system and digital elevation model. The book compares the more recent 25-meter digital elevation model and the older 100-meter digital elevation model. Statistical analysis of the two digital elevation models of Slovenia indicates that the smallest differences exist relative to surface heights, that there are larger differences relative to surface aspects, and that the largest differences exist relative to surface slopes.